Ramac Shallow Radar Profile Fimbulisen Ice Shelf 2009-2010 - Dens, Ruben; Kohler, Jack (Norwegian Polar Institute, 2016)
Ramac Radar Profile for the first season of the Fimbulisen project 2009-2010. ### Instruments - RAMAC GPR device by Malå Geoscience